HOW INSTITUTIONAL OWNERSHIP DRIVES FINANCIAL PERFORMANCE WHILE LARGER FIRMS STRUGGLE - Wulandari , Fischa Aditiyah; Suwarno, Suwarno (PT. Antis International Publisher, 2024)
General Background: Financial performance is a critical aspect of company evaluation, influenced by various internal and external factors. In the context of emerging markets, such as Indonesia, understanding the determinants of financial performance is crucial for both investors and policymakers. Specific Background: This study investigates the impact of institutional ownership, leverage, and company size on the financial performance of manufacturing technology sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023. Knowledge Gap: Although previous research has explored individual factors affecting financial performance, limited studies have concurrently examined institutional ownership, leverage, and company size within a specific sector in the Indonesian market. Aims: This research aims to elucidate the causal relationships between institutional ownership, leverage, and company size on financial performance, measured by Return On Assets (ROA), using a quantitative approach and multiple linear regression analysis. Results: The study finds that institutional ownership significantly positively impacts financial performance, suggesting that higher institutional supervision enhances management effectiveness and investor confidence. Conversely, leverage exhibits a negative but statistically insignificant effect, indicating it is not a major determinant of financial performance. Company size is found to have a significant negative effect, implying that larger firms may experience decreased financial performance due to potential inefficiencies in asset management. Novelty: This research provides a nuanced understanding of how institutional ownership, leverage, and company size interactively influence financial performance within the technology manufacturing sector in Indonesia, contributing new insights into sector-specific financial dynamics. Implications: The findings highlight the importance of institutional investors in enhancing company performance and suggest that larger firms may need to focus on improving asset management practices. Future research should explore additional variables and other sectors to enhance generalizability and provide broader insights into financial performance determinants.